2007
DOI: 10.1111/j.1567-1364.2007.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

The strange case of a biofilm-forming strain ofPichia fermentans, which controlsMoniliniabrown rot on apple but is pathogenic on peach fruit

Abstract: A biofilm-forming strain of Pichia fermentans proved to be most effective in controlling brown rot on apple fruit when coinoculated into artificial wounds with a phytopathogenic isolate of Monilinia fructicola. Culture filtrates and autoclaved cells had no significant influence on the disease. When sprayed onto the apple fruit surface, this yeast formed a thin biofilm but failed to colonize the underlying tissues. When inoculated into wounds artificially inflicted to peach fruit or when sprayed onto the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 38 publications
0
61
0
1
Order By: Relevance
“…The EPS substances provide protection to microorganisms by concentrating nutrients, enhancing resistance to stresses and preventing desiccation (Chmielewski and Frank, 2003;Prakash et al, 2003;Droby et al, 2009;Elias and Banin, 2012). The ability to form biofilms on the inner surface of wounds was indicated as a possible mechanism of biocontrol (Giobbe et al, 2007). However, little is known about the role of biofilms in the biocontrol activity of antagonistic yeast used to manage postharvest diseases and mechanisms involved in its formation (Droby et al, 2009).…”
Section: Biocontrol Assessment In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…The EPS substances provide protection to microorganisms by concentrating nutrients, enhancing resistance to stresses and preventing desiccation (Chmielewski and Frank, 2003;Prakash et al, 2003;Droby et al, 2009;Elias and Banin, 2012). The ability to form biofilms on the inner surface of wounds was indicated as a possible mechanism of biocontrol (Giobbe et al, 2007). However, little is known about the role of biofilms in the biocontrol activity of antagonistic yeast used to manage postharvest diseases and mechanisms involved in its formation (Droby et al, 2009).…”
Section: Biocontrol Assessment In Vivomentioning
confidence: 99%
“…However, little is known about the role of biofilms in the biocontrol activity of antagonistic yeast used to manage postharvest diseases and mechanisms involved in its formation (Droby et al, 2009). Giobbe et al (2007) observed that the biocontrol efficiency of Pichia fermentans (Lodder, Zentralblatt) against M. fructicola ((G. Winter) Honey) could therefore be due to the ability of yeast cells to remain adhered one to the other and to create a mechanical barrier (biofilm) interposing between the wound surface and the pathogen spore and germ tube, thus hampering infection by M. fructicola.…”
Section: Biocontrol Assessment In Vivomentioning
confidence: 99%
“…However, there are several issues to consider before marketing the bio-pesticides. For example, Giobbe et al [129] found that a biofilm-forming strain of Pichia fermentans proved to be most effective in controlling brown rot on apple fruit but pathogenic on peach fruit when co-inoculated into artificial wounds with a phytopathogenic isolate of M. fructicola. The authors, therefore, emphasized the need for a thorough risk assessment before allowing any deliberate release of bio-control agents, considering the associated potential effects, such as displacement of nontarget organisms, allergenicity to humans and other animals, toxicity, pathogenicity, and genetic stability.…”
Section: Biological Control Agentsmentioning
confidence: 99%
“…The authors, therefore, emphasized the need for a thorough risk assessment before allowing any deliberate release of bio-control agents, considering the associated potential effects, such as displacement of nontarget organisms, allergenicity to humans and other animals, toxicity, pathogenicity, and genetic stability. Hence, any minimal potential biohazard is inherent to the application of any bio-control agents [129] in peach commodity.…”
Section: Biological Control Agentsmentioning
confidence: 99%
See 1 more Smart Citation